Adding a reward increases the reinforcing value of fruit. Issue 4 (6th April 2017) - De Cock, Nathalie; Vervoort, Leentje; Kolsteren, Patrick; Huybregts, Lieven; Van Lippevelde, Wendy; Vangeel, Jolien; Notebaert, Melissa; Beullens, Kathleen; Goossens, Lien; Maes, Lea; Deforche, Benedicte; Braet, Caroline; et al.
Abstract: Adolescents' snack choices could be altered by increasing the reinforcing value (RV) of healthy snacks compared with unhealthy snacks. This study assessed whether the RV of fruit increased by linking it to a reward and if this increased RV was comparable with the RV of unhealthy snacks alone. Moderation effects of sex, hunger, BMI z -scores and sensitivity to reward were also explored. The RV of snacks was assessed in a sample of 165 adolescents (15·1 (sd 1·5) years, 39·4 % boys and 17·4 % overweight) using a computerised food reinforcement task. Adolescents obtained points for snacks through mouse clicks (responses) following progressive ratio schedules of increasing response requirements. Participants were (computer) randomised to three experimental groups (1:1:1): fruit ( n 53), fruit+reward ( n 60) or unhealthy snacks ( n 69). The RV was evaluated as total number of responses and breakpoint (schedule of terminating food reinforcement task). Multilevel regression analyses (total number of responses) and Cox's proportional hazard regression models (breakpoint) were used. The total number of responses made were not different between fruit+reward and fruit ( b −473; 95 % CI −1152, 205, P =0·17) or unhealthy snacks ( b 410; 95 % CI −222, 1043, P =0·20). The breakpoint was slightly higher for fruit than fruit+reward (HR 1·34; 95 % CI 1·00, 1·79, P =0·050), whereas no difference between unhealthy snacks and fruit+reward (HR 0·86; 95 % CI 0·62, 1·18, P =0·34) was observed. No indication of moderation was found. Offering rewards slightly increases the RV of fruit and may be a promising strategy to increase healthy food choices. Future studies should however, explore if other rewards, could reach larger effect sizes.